Hydrogen production via catalyst of green laser, molybdenum and ethanol - Azni, S. R. (Penerbit UTM Press, 2016)
Electrolysis is an electrochemical process which is known as a green technology. Laser irradiation and the presence of catalyst in water electrolysis are identified as ways of improving the efficiency and increment of hydrogen production. The enhancement of hydrogen production through water electrolysis is obtained by adding molybdenum to increase the current in electrochemical cell and ethanol as an agent in photochemical reaction. In addition, diode pumped solid-state laser green laser at 532 nm is employed with the purpose to compensate the residual electrical field effect. The combination of the three catalysts is found more powerful to cause water splitting, thus produced 5 times greater H2 production in comparison to the action of individual catalyst.